(ANALYSIS SITUATION APPLYING OF MANAGEMENT SERVICE TREATMENT OF HEALTH OF COMMUNITY: ADOLESCENT FRIENDLY OF REQUIREMENT HEALTH REPRODUCTIVE ADOLESCENT AGGREGATE IN SUB-DISTRICT OF TUGU, CIMANGGIS TOWN DEPOK) - Tantut Susanto (University of Muhammadiyah Malang, 2011)
Adolescent group as a group at risk in community during a period of growth transition and development require caring which totally and is inwrought. Caring adolescent through adolescent friendly related to health of adolescent reproduction. Aim of this situation analysis is depicting of service management system execution health of treatment of adolescent friendly in community in Sub-District of Tugu Cimanggis Town Depok. This adolescent analysis situation reproduction medicare emphasized at analysis four factors, that is strength, weakness, opportunity, and threat an organization in adolescent treatment. Result of analysis there are problem of is fourth of management function, that is planning function, organizational, directing, and controlling of health of adolescentreproduction in adolescent friendly. This matter need the existence of health service reproduce in community through adolescent peer group in community in the effort improving knowledge, attitude, and is skilled of adolescent life in health of reproduction.